At the outer limits of the international: Orbital infrastructures and the technopolitics of planetary (in)security. (October 2020) - Peoples, Columba; Stevens, Tim
Abstract: As staples of science fiction, space technologies, much like outer space itself, have often been regarded as being 'out there' objects of international security analysis. However, as a growing subset of security scholarship indicates, terrestrial politics and practices are ever more dependent on space technologies and systems. Existing scholarship in 'astropolitics' and 'critical astropolitics' has tended to concentrate on how such technologies and systems underpin and impact the dynamics of military security, but this article makes the case for wider consideration of 'orbital infrastructures' as crucial to conceptions and governance of planetary security in the context of the 'Anthropocene'. It does so by outlining and analysing in detail Earth Observation (EO) and Near-Earth Object (NEO) detection systems as exemplary cases of technological infrastructures for 'looking in' on and 'looking out' for forms of planetary insecurity. Drawing on and extending recent theorisations of technopolitics and of Large Technical Systems, we argue that EO and NEO technologies illustrate, in distinct ways, the extent to which orbital infrastructures should be considered not only part of the fabric of contemporary international security but as particularly significant within and even emblematic of the technopolitics of planetary (in)security.